Enhanced efficiency with CDCA co-adsorption for dye-sensitized solar cells based on metallosalophen complexes. (October 2020) - Zhang, Jie; Zhong, Aiguo; Huang, Guobo; Yang, Meiding; Li, Dan; Teng, Mingyu; Han, Deman
Highlights: Salophen type Schiff base metal complexes were prepared with anchor group. Their performances in dye-sensitized solar cells depend on the soaking solvents. The CDCA co-adsorbent could inhibit dyes aggregations for better cell performances. Abstract: The condensation of 4-diethylaminosalicylaldehyde and 3, 5-di- tert -butyl-salicylaldehyde with 3, 4-diaminobenzoic acid afforded two salophen type Schiff base ligands, L1 and L2, respectively. Subsequently, their corresponding platinum(II) and zinc(II) salophen complexes (PtL1, PtL2, ZnL1 and ZnL2) were synthesized through the reaction of the two salophen ligands with potassium tetrachloroplatinate(II) and zinc(II) acetate, respectively. The structures of the metallosalophen complexes were characterized by 1 H NMR, infrared spectroscopy and high-resolution mass spectrometry. Their photophysical properties and cyclic voltammetry behaviours were investigated in detail. Using these complexes as photosensitizers, the dye-sensitized solar cells (DSSCs) were prepared and inferior performances were recorded due to their planar structures and significant aggregations. Upon the addition of chenodeoxycholic acid (CDCA) as co-adsorbents, the aggregation behaviours could be effectively inhibited and the cell performances could be enhanced with the highest power conversion efficiency up to 2.57% for PtL1. Considering the simplicity in the preparation and the structure variability, these metallosalophen complexes represent a new class of photosensitizers for DSSC applications.